Low Orbit Satellite Internet of Things Transmission Technology Based on LoRa - Zehao LI; Jianpeng MA; Shun ZHANG; Xiao WEI; Jing ZHANG (天地一体化信息网络)
As an emerging wide area network technology, LoRa has the characteristics of low power consumption and wide coverage.It has very broad prospects in the field of internet of things applications.In recent years, it has been deployed in countless objects around the world.The advantages of wide coverage of low-orbit satellite networks make it an inevitable technology to achieve global coverage of massive internet of things.Firstly, the basic principles of LoRa technology were expounded.Then the problems existed after the LoRa technology was directly introduced into the low-orbit satellite IoT were analyzed.Finally, a set of LoRa transmission technology suitable for low-orbit satellite IoT was proposed, focused on solved the problem of LoRa frame synchronization under the condition of low-orbit long-distance low-power transmission, and the problem of LoRa demodulation caused by the high-speed movement of satellites due to the Doppler frequency off set.The simulation results showed that the proposed joint synchronization and frequency off set estimation algorithm could obviously improved the synchronization probability and transmission reliability of LoRa technology under the conditions of extremely low SNR and large Doppler frequency shift.